A neutrino mass model with hidden U(1) gauge symmetry - Haiying Cai; Takaaki Nomura; Hiroshi Okada (Nuclear Physics B, 2019)
We propose a realisation of inverse seesaw model controlled by hidden U(1) gauge symmetry, and discuss the impact of a bosonic dark matter (DM) candidate by imposing a Z2 parity. We present the detail of scalar spectra and apply the Casas-Ibarra parametrisation to fit the neutrino oscillation data. For this model, the allowed region is extracted to explain the observed relic density and the muon g−2 discrepancy, satisfying flavor constraints with DM involved. We interpret the DM annihilation into f¯f including all SM charged fermions and investigate the direct detection to place the bound on DM-Higgs coupling. Finally the LHC DM production is explored in light of charged lepton pair signature plus missing transverse energy.